Ginsenoside Rg3-enriched red ginseng extract inhibits platelet activation and in vivo thrombus formation - Jeong, Dahye (J Ginseng Res, 2017)
BACKGROUND: Korean Red Ginseng has been used for several decades to treat many diseases, enhancing both immunity and physical strength. Previous studies have documented the therapeutic effects of ginseng, including its anticancer, antiaging, and anti-inflammatory activities. These activities are mediated by ginsenosides present in the ginseng plant. Ginsenoside Rg3, an effective compound from red ginseng, has been shown to have antiplatelet activity in addition to its anticancer and anti-inflammatory activities. Platelets are important for both primary hemostasis and the repair of the vessels after injury; however, they also play a crucial role in the development of acute coronary diseases. We prepared ginsenoside Rg3-enriched red ginseng extract (Rg3-RGE) to examine its role in platelet physiology. METHODS: To examine the effect of Rg3-RGE on platelet activation in vitro, platelet aggregation, granule secretion, intracellular calcium ([Ca(2+)](i)) mobilization, flow cytometry, and immunoblot analysis were carried out using rat platelets. To examine the effect of Rg3-RGE on platelet activation in vivo, a collagen plus epinephrine-induced acute pulmonary thromboembolism mouse model was used. RESULTS: We found that Rg3-RGE significantly inhibited collagen-induced platelet aggregation and [Ca(2+)](i) mobilization in a dose-dependent manner in addition to reducing ATP release from collagen-stimulated platelets. Furthermore, using immunoblot analysis, we found that Rg3-RGE markedly suppressed mitogen-activated protein kinase phosphorylation (i.e., extracellular stimuli-responsive kinase, Jun N-terminal kinase, p38) as well as the PI3K (phosphatidylinositol 3 kinase)/Akt pathway. Moreover, Rg3-RGE effectively reduced collagen plus epinephrine-induced mortality in mice. CONCLUSION: These data suggest that ginsenoside Rg3-RGE could be potentially be used as an antiplatelet therapeutic agent against platelet-mediated cardiovascular disorders.